A descriptive study to explore working conditions and childcare practices among informal women workers in KwaZulu-Natal, South Africa: identifying opportunities to support childcare for mothers in informal work - Christiane Horwood; Lyn Haskins; Laura Alfers; Zandile Masango-Muzindutsi; Richard Dobson; Nigel Rollins (BMC, 2019)
Abstract Background Although women working in the informal economy are a large and vulnerable group, little is known about infant feeding and childcare practices among these women. The aim of this study was to explore childcare practices among mothers in informal work. Methods A cross-sectional survey among mothers with children aged < 2 years working in the informal economy in an urban and a rural site in KwaZulu-Natal, South Africa. Participants were selected using purposive and snowball sampling. Results A total of 247 interviews were conducted with 170 informal traders and 77 domestic workers. Most mothers lived with their child (225/247, 91.1%), had initiated breastfeeding (208/247; 84.2%) and many were still breastfeeding (112/247; 45.3%). Among 96 mothers who had stopped breastfeeding, the most common reason was returning to work (34/96; 35.4%). Many mothers relied on family members, particularly grandmothers, to care for their child while they were working (103/247, 41.7%) but some mothers took their child with them to work (70/247; 28.1%). Few fathers participated in the care of their child: 54 mothers (21.9%) reported that the father had ever looked after the child while she was away from home. Domestic workers were less likely than informal traders to take their child to work (p = 0.038). Women reported receiving a salary from an informal employer (119), or being own-account workers (120) or being unpaid/paid in kind (8). Most participants were in stable work (> 4 years) with regular working hours, but received very low pay. Domestic workers were more likely than informal traders to have regular working hours (p = 0.004), and to be earning >$240 per month (p = 0.003). Mothers reported high levels of food insecurity for themselves and their child: 153 mothers (61.9%) reported having missed a meal in the past month due to lack of resources to buy food, and 88 (35.6%) mothers reported that their child had missed a meal for this reason. Conclusion This study provides a preliminary description of informal women workers who, despite having stable work, are vulnerable, low paid and food insecure. These women may require support to provide optimal childcare and nutrition for their children.